Autoimmune Thyroid Disease is Associated with a Lower Prevalence of Diabetic Retinopathy in Patients with Type 1 Diabetic Mellitus - Stefanowicz-Rutkowska, Magdalena Maria (Medicina (Kaunas), 2020)
Background and objectives: The aim of the study was to assess the correlation of autoimmune thyroid diseases (AITD) in patients with diabetes mellitus type 1 (DM1) with the occurrence of diabetic retinopathy (DR). Materials and Methods: The inclusion criteria for the study were: type 1 diabetes diagnosed on the basis of WHO criteria lasting at least a year, presence of AITD for at least a year, and age over 18 years. The control group consisted of patients without diagnosed AITD (DM1noAITD), selected according to age, BMI and DM1 duration. Anthropometric parameters, metabolic risk factors such as glycated hemoglobin (HbA1c), lipids and blood pressure, thyroid status and the presence of DR were assessed. Results: The study involved 200 patients with type 1 diabetes aged 36 ± 12 years, 70 men and 130 women. Patients from the study group (DM1AITD) had significantly lower creatinine concentration, significantly lower systolic blood pressure (SBP), glycated hemoglobin (HbA1c) percentage and triglyceride (TG) concentration, and higher high-density lipoprotein (HDL-cholesterol) concentration than the control group (DM1noAITD). There was a significantly lower chance of non-proliferative diabetic retinopathy (NPDR) among DM1AITD than in the control group. Conclusions: Patients with DM1 and AITD were metabolically better balanced, as evidenced by a significantly lower SBP, percentage of HbA1c and TG, as well as significantly higher HDL-cholesterol in this group. Patients with DM1 and AITD were significantly less likely to have NPDR than the control group.